Analysis of literature review on factors influencing the adoption of telecommuting - Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin (2012)
Telecommuting is increasingly being perceived as a viable travel demand management strategy that aims to reduce peak hour traffic congestion by allowing commuters to work from home or a nearby telecommuting centre on certain days of the week. The increasing private vehicle usage by International Islamic University Malaysia (IIUM) community is posing a strain on the ability of the existing road and the related infrastructure to cope with the increasing traffic volume and parking demand within the campus. Due to the diverse travel patterns and work characteristics of IIUM employees, adoption of telecommuting by staffs is perceived as a potential means of reducing the peak hour traffic in IIUM. The aim of this study is to investigate the perceptions of IIUM employees on various aspects of telecommuting. This paper, however, highlights on the rationale behind the study and literature background of telecommuting aspects especially on factors influencing the preference towards telecommuting.